2022
DOI: 10.3389/fpsyt.2022.862958
|View full text |Cite
|
Sign up to set email alerts
|

A Triple-Network Dynamic Connection Study in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) was associated with abnormal organization and function of large-scale brain networks. We applied group independent component analysis (Group ICA) to construct the triple-network consisting of the saliency network (SN), the central executive network (CEN), and the default mode network (DMN) in 25 AD, 60 mild cognitive impairment (MCI) and 60 cognitively normal (CN) subjects. To explore the dynamic functional network connectivity (dFNC), we investigated dynamic time-varying triple-networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…This is a consistent finding, with altered DMN-CEN connectivity in schizophrenia (Manoliu et al, 2013a), major depressive disorder (Manoliu et al, in review), Alzheimer's disease (Meng et al, 2022), and bipolar disorder (Wang et al, 2020). Dynamic changes in network interactions also occur in schizophrenia (Supekar et al, 2019) and Alzheimer's disease (Meng et al, 2022). Crucially, insular dysfunction correlates with aberrant DMN-CEN interactions in schizophrenia and major depressive disorder (Manoliu et al, 2013a;Manoliu et al, in review), directly linking SN abnormalities to impaired cross-network coordination.…”
Section: Network Interactions and Psychopathologysupporting
confidence: 75%
See 1 more Smart Citation
“…This is a consistent finding, with altered DMN-CEN connectivity in schizophrenia (Manoliu et al, 2013a), major depressive disorder (Manoliu et al, in review), Alzheimer's disease (Meng et al, 2022), and bipolar disorder (Wang et al, 2020). Dynamic changes in network interactions also occur in schizophrenia (Supekar et al, 2019) and Alzheimer's disease (Meng et al, 2022). Crucially, insular dysfunction correlates with aberrant DMN-CEN interactions in schizophrenia and major depressive disorder (Manoliu et al, 2013a;Manoliu et al, in review), directly linking SN abnormalities to impaired cross-network coordination.…”
Section: Network Interactions and Psychopathologysupporting
confidence: 75%
“…Critically, the triple network model proposes aberrant SN dysfunction disrupts normal interactions between the DMN and CEN. This is a consistent finding, with altered DMN-CEN connectivity in schizophrenia (Manoliu et al, 2013a), major depressive disorder (Manoliu et al, in review), Alzheimer's disease (Meng et al, 2022), and bipolar disorder (Wang et al, 2020). Dynamic changes in network interactions also occur in schizophrenia (Supekar et al, 2019) and Alzheimer's disease (Meng et al, 2022).…”
Section: Network Interactions and Psychopathologysupporting
confidence: 65%
“…The spatial ICA can identify spatially separated but functionally synergistic intrinsic connectivity networks. With advances in image analysis technology, dynamic functional network connectivity (dFNC) analysis based on group ICA has been extensively employed to study neurological and psychiatric illnesses, such as Parkinson's disease (PD) (Fiorenzato et al, 2019), Alzheimer's disease (AD) (Meng et al, 2022), epilepsy (Liu et al, 2017), schizophrenia (Yang et al, 2022), and depressive disorder (Demirtaş et al, 2016). The dFNC analysis provides additional neuroimaging metrics and time property information, including state analysis (temporal features and FC strength) and topological organization variance, which cannot be obtained from static functional network connectivity (FNC) (Fu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The SN is part of an integral mediation hub that affects dynamic interactions between the DMN and CEN networks. Numerous studies have demonstrated that altered triple-network models (DMN, SN, and CEN) are the prominent hallmarks of both AD and MCI ( Meng et al, 2022 ). Further, multiple neuroimaging trials have suggested that regulating the activities of triple-network models is a key mechanism by which acupuncture therapy affects brain functioning ( Bai et al, 2009 ; Deng et al, 2016 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%